Tempted by the boss - Bennett, Jules (Texas Cattleman's Club: rags to riches., 2020)
"Kelly Prentiss needs her workaholic boss, Luke Holloway, to relax--and see her as more than his assistant. So she arranges him an island vacation--with her! And just as she fantasized, the island heat ignites a passion that makes seduction irresistible. But once they're home--amid a scandal about to take down his family's company--will it be back to business as usual?--"